The Future of Hybrid Work: A Bibliometric Mapping of Employee Productivity and Well-Being - Judijanto, Loso; Muhtadi, Muhamad Ammar; Arini, Rani Eka (West Science Social and Humanities Studies, 2025)
This bibliometric analysis explores the significant impact of hybrid work on employee productivity and well-being, drawing on a comprehensive review of literature sourced from the Scopus database. The study highlights the evolution of hybrid work themes from 2000 to 2025, illustrating the shift from traditional telecommuting to integrated hybrid models that focus on both organizational efficiency and employee satisfaction. By mapping keyword occurrences and author collaborations, the research identifies key trends and gaps in the existing literature, offering insights into the interdisciplinary nature of hybrid work studies. The findings suggest that while hybrid work arrangements can enhance productivity and flexibility, they also present challenges such as maintaining work-life balance, ensuring employee engagement, and managing a dispersed workforce. The study emphasizes the need for organizations to develop robust strategies that leverage technology and foster an inclusive culture to fully realize the benefits of hybrid work models. Future research directions are proposed to further investigate the long-term effects of hybrid work on different sectors and cultures, aiming to refine and optimize these work arrangements.